Differences in Limb Muscle Strength Affecting Vertical Jump Heights in Soccer Players after Chronic Ankle Injury - Anggara Dwi Samudra; Bambang Purwanto; Dwikora Novembri Utomo (Journal of Modern Rehabilitation)
Introduction: Muscle strength strongly affects soccer players’ activities, but chronic ankle injuries can reduce the ability of athletes to achieve their best performance. No report exists in the literature about the role of certain muscles in affecting the vertical jump height of soccer players. Therefore, this study aimed to analyze the differences in leg muscle strength that affect the vertical jump height of soccer players after chronic ankle injury. Materials and Methods: To achieve the aim of this study, a cross-sectional design was employed by involving one team consisting of 25 Surabaya Football Association (PERSEBAYA) players. They were divided into injury and noninjury groups, according to the questionnaire. The participants were determined based on their normal body mass index (BMI), age (17-40 years), male gender, and PERSEBAYA players. The collected data included vertical jump, ankle muscle construction, and hamstring muscle data. The data were statistically analyzed using the t test and Pearson correlation (P<0.05). Results: There was no significant difference in leg muscle strength between the injured and uninjured players. Only the hamstring muscle significantly affected soccer players’ vertical jump after chronic ankle injury (r=0.422, P=0.035 with moderate influence) and was not affected by the gastrocnemius, plantar, adductor, and abductor muscles. Conclusion: There was a correlation between eccentric contraction of the hamstring muscle and vertical jump height in soccer players after a chronic ankle injury. These findings benefit soccer practitioners and medical teams in designing injury management and recovery strategies for players with ankle injuries.